Bimbingan Konseling Pada Anak Usia Dini : Straegi Dan Manfaatnya Dalam Pengembangan Holistik - Fauziah Nasution; Syahdia Shinta Simanjuntak; Salsabilah Salsabilah; Yola Adela Sindy (Jurnal Ilmiah Wahana Pendidikan, 2023)
This journal discusses the important role of counseling guidance in the holistic development of early childhood. Early childhood is a critical stage of development that affects their cognitive, social, emotional and physical aspects. In this journal, we highlight effective guidance and counseling strategies in supporting early childhood development. In addition, we discuss the benefits of counseling in helping young children overcome developmental challenges and build strong social-emotional skills. This research illustrates the importance of collaboration between counselors, teachers, and parents in providing appropriate counseling guidance to early childhood. It is hoped that a better understanding of the role of guidance and counseling in early childhood development can make a positive contribution in promoting children's well-being and future success.